Maya Index dan Kepadatan Larva Aedes aegypti di Daerah Endemis Demam Berdarah Dengue Kelurahan Labuh Baru Timur Kecamatan Payung Sekaki Kota Pekanbaru - Esy Maryanti; Suri Dwi Lesmana; Dhewa Triguna; Martin Plymoth; Wida Harmas; Delly Delly; Afiata Afiata; Mislindawati Mislindawati (Fakultas Kedokteran Universitas Riau, 2018)
Dengue hemorrhagic fever (DHF) is an infectious disease that can result in death, caused by dengue virus and transmitted through Aedes aegypti mosquitoes. The incidence of dengue fever every year, requires more serious attention to increasing awareness of the disease. The purpose of this study was to determine the Maya Index (MI) and density of Aedes aegypti larvae in Labuh Baru Timur subdistrict, Payung Sekaki, Pekanbaru city. Method of the reseach was survey research using questionnaire and larva identification using single larva method method. A total of 131 houses that have been surveyed got 589 containers. MI status based on breeding risk index and hygiene risk index, found high as many as 23 houses (17.58%). Free number of larvae of 67.94, Container index (CI) of 8.32, House Index (HI) 32.06 and Breteau index of 37. HI and CI figures are still high that has not met the government target. The density of larvae is on the 3 - 5 scale, ie the medium category, meaning that the area has a medium transmission risk to the spread of DHF.